Publication trends and green cosmetics buying behaviour: A comprehensive bibliometric analysis - Mamta; Gyan Prakash (Heliyon)
Green cosmetics have gained increasing attention in the research community. This study conducts a comprehensive review of 164 publications from the past decade (2011–2022) to provide an up-to-date analysis of consumer purchasing behaviour regarding green cosmetics. It examines consumers' purchasing decisions, performance, and intellectual frameworks and identifies the field's most influential journals, prolific authors, institutions, and nations. The study also sheds light on five critical themes related to green cosmetics buying behaviour: environmental concern, green marketing, sustainable consumption, green cosmetics, and green consumerism. By offering insights into these aspects, this research contributes to the knowledge base for future studies, aids policymakers, and assists marketing managers in promoting green cosmetics buying behaviour.